Conversion of stereo recording to 5.1 format using head-related transfer functions - HEN, Paweł; KIN, Maurycy J.; PLASKOTA, Przemysław (Archives of Acoustics, 2008)
The paper presents the conversion of stereo recordings into multi-channel format 5.1 by means of the HRTF filtering. An algorithm of additional channels preparation (a central one and two surround ones) using various filters created on the base of HRTF was tested. The filter bank was prepared on the basis of impulse responses given by users. The algorithm uses the impulse response convolution of the filter with a processed signal. The convolution is realized in frequency domain, i.e. Fourier transforms of the processed signals are multiplied. Recordings created in such way were tested for the features of sound color distortion and spaciousness of the audio-scene in frontal plane.